Determinants of temporal change in telomere length and its associations with chronic complications and mortality in type 2 diabetes: the Fremantle diabetes study phase II - Chieh-Hsin Yang; Michael L H Huang; Wendy A Davis; Alicia J Jenkins; Timothy M E Davis (Cardiovascular Diabetology)
Abstract Background Relative telomere length (rTL), a biomarker of biological ageing, has been implicated in type 2 diabetes and its complications. We aimed to identify the associates of rTL change over 4 years (∆rTL), and to investigate whether rTL and ∆rTL are associated with complications and mortality in adults with type 2 diabetes from the Australian observational community-based Fremantle Diabetes Study Phase II (FDS2). Methods Participants (n = 819) from the FDS2 cohort had baseline and Year-4 (mean ± SD 4.2 ± 0.4 years) rTL measured by qPCR (intra- and inter-assay %CV: 0.56% and 2.69%, respectively). The rTL change (∆rTL; % change/year) was categorised as Shortened (< − 2.69%), Unchanged (− 2.69% to + 2.69%) or Lengthened (> + 2.69%). Multiple logistic regression identified clinical and biochemical determinants of ∆rTL Shortened versus Not Shortened (Unchanged plus Lengthened). rTL and ∆rTL (continuous and categorical) were added to Cox and competing risk regression models of conventional predictors of major complications, CVD death and all-cause mortality during a mean ± SD 11.5 ± 2.1 years of follow-up. Results rTL was inversely correlated with age (r = − 0.186, P < 0.001). ∆rTL was shortened in 25.5% subjects, unchanged in 10.5%, and lengthened in 64.0%. Shortening was associated with older age, male sex, smoking, obesity, lipid-modifying drug use, and higher platelet count and serum bilirubin levels (P < 0.05). There were no statistically significant unadjusted or age- and sex-adjusted associations between baseline rTL, Year-4 rTL, or ∆rTL, and any incident micro- or macrovascular complications. In unadjusted Cox regression, ∆rTL lengthening was associated with a lower risk of CVD death (hazard ratio 0.98 (0.97, 0.99), P = 0.042) but this association became non-significant after adjustment for conventional risk factors. Conclusions In adults with type 2 diabetes, rTL does not always shorten over time. rTL and ∆rTL were associated with baseline conventional cardiometabolic risk factors but not independently with major incident complications. There was a weak association between ∆rTL and CVD mortality. These findings question the utility of rTL and ∆rTL in usual type 2 diabetes care.